MATH Mastery: Development of 2D Mathematics Learning Application for Matriculation Students - ANWAR, NURUL SYAFIQAH FARHANAH; Muhammad Fakri Othman (Applied Information Technology And Computer Science, 2025)
The MATH Mastery application solves fundamental issues encountered by Malaysian matriculation students when studying mathematics, such as fragmented tools and a lack of real time feedback. This study is to develop 2D mobile learning application adapted to the matriculation syllabus, develop it  with gamified approach on the Android platform using Unity and C#. The approach used in the development was Multimedia Mobile Content Development (MMCD). Findings indicate that gamification and real-time feedback considerably improve engagement, learning efficiency, and satisfaction with the application. The study finds that MATH Mastery provides an integrated and engaging learning platform, with possible future enhancements such deeper chapter material, improved gamification components, and broader usability testing. The average score of respondents using the System Usability Scale (SUS) was 72.25% which falls in acceptable range. To improve learning outcomes and user engagement, future work will include cross-platform support, AI-driven hints, extended content modules, and extensive longitudinal research.